Intelligent Tutor with Emotion Recognition and Student Emotion Management for Math Performance - Maria Lucia Barron Estrada; Ramón Zatarain Cabada; Yasmín Hernández Pérez (Universidad Autónoma de Baja California, 2014)
This research presents the development, implementation, and testing of an Intelligent Tutoring System for math in third grade elementary students, it identifies and manages the emotional state of the student; it produces affective feedback for the student during the course that also it is part of a social network. Emotions are recognized via facial expressions by means of an artificial neural network. The social network and the intelligent tutoring system with affective management have been tested in public and private elementary schools with very satisfying results.